HUBUNGAN KONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS AMBACANG KOTA PADANG TAHUN 2016 - Febrianti, Rini (Menara Ilmu, 2017)
Anemia may decrease health status and mothers welfare and increase risks that bringdisadvantages to both mothers and infant. In Indonesia (2015) 41.8% pregnant womensuffered from anemia. Fe tablet supplementation during pregnancy is of the best way toincrease Hb level to prevent anemia. This study aimed to evaluate the relationship between Fetablet consumption and anemia prevalence in pregnant women in Puskesmas AmbacangPadang in 2016. This study was an analytical study using cross-sectional design. Thepopulation was pregnant women in first and second trimester, and as much as 42 samplesparticipated in this study. Data was collected by interview and Hb level test using Hb Sahli set.Data was analyzed using Chi-Square test. This study was conducted in March-November2016. The results found 61.9% od respondent suffered from anemua and 38.1% had noanemia. 50% of respondent consumed Fe tablet, while the other 50% didn’t. Chi square testshowed no relationship between Fe tablet consumption and anemia (p value=0,.751). Thisstudy showed no relationship between Fe tablet consumption and anemia. However, a lot ofpregnant women consumed Fe tablet in a wrong way. Therefore, we suggest the clinician inPuskesmas Ambacang to give direct health promotion to pregnant women or through cadres,not only about the advantages and side effects of consuming Fe tablet, but also about how toconsume Fe tablet in the right way and Fe intake that may be obtainedfrom daily food soanemia could be prevented.Keywords: Fe tablet consumption, anemia